História cultural da comunidade surda de Manaus: resgate baseado em fontes orais - Costa, Tatyana Sampaio Monteiro Pessoa da (2023)
Deaf culture and the history of many deaf communities is related to educational policies that, in some way, favored deaf-deaf contact in schools (LADD, 2003). In this sense, knowing the history of deaf education can bring us closer to the cultural history of the deaf and sign languages. The aim of this research is to survey facts about the history of deaf education in Manaus that favored the consolidation of a deaf community. More specifically, the objectives are to collect information about the emergence and functioning of educational institutions aimed at the deaf in Manaus, to identify facts in the history of deaf education that favored the emergence of a deaf community and to trace a trajectory on these facts that favored contact between deaf people, culture and deaf identities. The time frame for surveying the history of deaf education in Manaus and, consequently, of the deaf community in Manaus, involves the beginning of the second half of the 20th century, that is, approximately, the period from 1950 to 1980. The collection of information took place from the analysis of narratives of deaf people, mostly elderly, which were collected from interviews, and, in a complementary way, from the analysis of institutional documents, newspapers and photographs from the personal collection of the interviewees. After analyzing and systematizing the data, we describe the Instituto Montessoriano Álvaro Maia, Apae, Escola Estadual Augusto Carneiro dos Santos and Instituto Filippo Smaldone Manaus, from the perspective of the participants. We also describe the trajectory of the missionary Fr. Eugênio Oates in his relationship with the deaf community in Manaus.